Host susceptibility evaluation against the major insect pests in Chilli (Capsicum annuum L.) ecosystem and their eco-friendly management - Pathak, Mahesh (Umiam : CPGSAS, CAU(Imphal), 2024)
Chilli (Capsicum annuum L.) is a vital spice and vegetable crop cultivated world wide. However, its productivity and overall yield are significantly affected by various factors, with insect pest attacks being the most critical issue.The diversity of insect species in Chilli ecosystem was studied during March-June, 2024 in three different locations viz., Umsning, Nongpoh and Bhoirymbong under Ri-bhoi district of Meghalaya. A total of 27 species of insect pests were recorded belonging to 6 orders and 15 families. Among the insect pest, aphids, Aphis gossypi and Myzus persicae recorded the highest relative abundance of 30.19 % and 27.68 % respectively. This was followed by thrips, Scirtothrips dorsalis (8.94 %), whitefly, Bemisia tabaci (3.71 %), fruit borer, Helicoverpa armigera (3.45 %) and mealybug, Ferrisia virgata (2.82 %). A total of 11 species of natural enemies were recorded which belongs to 4 orders and 5 families. Among the natural enemies, Coccinella septumpunctata recorded the highest relative abundance of 16.66 %. A total of eight species of pollinators were recorded, among which honeybee (Apis spp.) recorded the highest relative adundance of 21%. The studies on correlation of major insect pests (aphids, whitefly, thrips and fruit borer) with weather parameters exhibited that peak temperature and relative humidity had significant positive correlation (r=0.196 and r=0.355). In vitro evaluation of six different Chilli cultivars against the major sucking pests (aphids and whiteflies) conducted in the greenhouse of CPGS-AS, Umiam, Meghalaya, revealed significant variation in host susceptibility. The cultivar Arka Khyati exhibited the lowest susceptibility with an average of (94 aphids/plant) and (15.66 aphids/leaf) and exhibited minimal damage, indicated by leaf distortion and chlorosis damage index (0.33), honeydew (0.00) and Stunting (0.66). Variety, IPBC-313 exhibited the highest susceptibility, with an average of 430 aphids/plant and 71.66 aphids/leaf, along with severe damage, indicated by mean leaf distortion damage index (4.33), chlorosis (3.33), honeydew (4.33) and stunting (2.33). Variety, Arka Khyati also exhibited the highest resistance to whiteflies, with an average of 2.99 whiteflies settlement and an infestation index of 0.66 whereas, IPBC-313 had the highest infestation with an average of 16.00 whiteflies settlement and an infestation index of 5.00, categorizing it as highly susceptible. The evaluation of biopesticides and chemicals against major insect pests of Chilli conducted at the experimental field, Sumer, Umbang, Meghalaya showed that among the biopesticides, Azadirachtin 0.15 % EC, Metarhizium robertsii and Lecanicillium lecanii were found efficient against the sucking pests of Chilli (50.23 %, 48.97 % and 45.18 % reduction of population over the control). Whereas, maximum percent reduction of fruit-borer population over control was observed in plots treated with Bacillus thuringensis var. kurstaki (53.09 %) and the mean per cent of damaged fruits was also lowest in the plots treated with Bacillus thuringensis var. kurstaki (4.82 %), thus minimizing fruit damage in Chilli. The highest marketable yield (67.88 q/ha) and B:C ratio (3.30:1) was achieved from the chemically treated plots i.e., Imidacloprid 17.8 % SL followed by Bacillus thringensis var. kurstaki (59.22 q/ha, B:C ratio: 2.90:1), Metarhizium robertsii (55.33 q/ha, B:C ratio: 2.72:1) and Beauveria bassiana (53.11 q/ha, B:C ratio: 2.62:1) respectively. Although the synthetic pesticides recorded the highest yield and B:C ratio but bio-pesticides can be used in lieu of the conventional insecticides in management of insect pests of Chilli, thereby minimising the hazardous effects of chemical insecticides.
Includes bibliographical references.
Keywords: Chilli -- Insect pest -- Management; Capsicum annuum L